The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4236/abb.2013.47a2001
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of plant methanolic extracts on a field isolate of <i>Pseudomonas syringae</i> pvtomato from the Casablanca region (Morocco)

Abstract: A bacterial field isolate recovered from infected tomato plants in a green-house at Sidi Rehal, a region near Casablanca city (Morocco), was identified as the gammaproteobacterium Pseudomonas syringae pv. tomato DC3000 strain, the causal agent of bacterial speck. The bacterial isolate was characterized by morphological, biochemical and molecular biological tests, its growth curves carried out in various culture media, and its phytopathogenicity verified by infection tests. A screening was performed to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…These results are in agreement with our previous study which has reported the antibacterial effect of hydro-methanolic extracts of leaves and seeds of C. australis 14 , as far as various extracts from this plant against S. aureus, P. aeruginosa, E. coli and B. subtilis 16 , S. aureus and P. aeruginosa 8 , P. syringe 17 and S. aureus, L. monocytogenes, P. aeruginosa and E. coli 18 . Antifungal potential: As shown in Table 5, a significant and dose-dependent antifungal effect was obtained with all extracts tested.…”
Section: Antibacterial Potentialsupporting
confidence: 94%
“…These results are in agreement with our previous study which has reported the antibacterial effect of hydro-methanolic extracts of leaves and seeds of C. australis 14 , as far as various extracts from this plant against S. aureus, P. aeruginosa, E. coli and B. subtilis 16 , S. aureus and P. aeruginosa 8 , P. syringe 17 and S. aureus, L. monocytogenes, P. aeruginosa and E. coli 18 . Antifungal potential: As shown in Table 5, a significant and dose-dependent antifungal effect was obtained with all extracts tested.…”
Section: Antibacterial Potentialsupporting
confidence: 94%
“…; Elkhalfi et al . ), followed by the detection of the h ypersensitivity r esponse and p athogenicity‐associated Z gene ( hrpZ ; Zaccardelli et al . ) and citrate synthase ( gltA ) (Hwang et al .…”
Section: Methodsmentioning
confidence: 99%
“…tomato infection were collected from three tomato-producing regions in south-east Queensland, Australia. Species identification followed standard biochemical methods for the determination of P. syringae (Lelliott et al 1966;Elkhalfi et al 2013), followed by the detection of the hypersensitivity response and pathogenicity-associated Z gene (hrpZ; Zaccardelli et al 2005) and citrate synthase (gltA) (Hwang et al 2005;Berge et al 2014) using gene-specific PCR amplification and subsequent DNA sequencing. Reaction conditions for the PCRs varied slightly to those originally published (Table S1).…”
Section: Bacterial Isolate Details and Preparationmentioning
confidence: 99%
“…An ethanolic extract was slightly active against B. subtilis and S. haemolyticus, but was inactive against other Gram positive and Gram negative strains, resulting in no further studies with this extract [20]. Furthermore, only weak activity was achieved by methanolic extracts of this plant against P. syringae [74].…”
Section: Human Pathogensmentioning
confidence: 97%